Interdependency and Priority of Critical Infrastructure Information (Case Study: Indonesia Payment System) - Arini Muhafidzah; Kalamullah Ramli (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
The sturdy and reliable payment system is one of the most important systems in the digitalization era, especially in the pandemic COVID-19 period. As part of Critical Infrastructure Information (CII), a strategy to protect the payment system is needed to reduce risks that may arise. But the author's best knowledge, in Indonesia, no reference describes the interdependency of the CII sector that could be used as input on strategy making for reducing the risk on all CII sectors which are influencing the payment system. This research uses the Fuzzy-based DANP (FDANP) Framework based on a multi-expert perspective on inter-sector influences to identify the interdependency and priority of the CII sector with a case study on the payment system. The contribution of this research is to provide information about the interdependency and priority of the CII sector. The findings of this research show that 5 sectors that have an influence on other sectors with a case study of the payment system and the information and communication technology sector, the energy and mineral resources sector, and the financial sector are the three major sectors that must be paid more attention to because they have an impact on many sectors.